Acupuncture for the Treatment of Chronic Pain in the Military Population: Factors Associated With Treatment Outcomes. Issue 10 (October 2017) - Plunkett, Anthony; Beltran, Thomas; Haley, Chelsey; Kurihara, Connie; McCoart, Amy; Chen, Louis; Wilkinson, Indy; Cohen, Steven P.
Abstract : Objectives: Acupuncture is characterized as an alternative or complementary medicine with a low complication rate and minimal side effects. There is a lack of robust evidence that shows acupuncture is an effective treatment for chronic pain. The purpose of this study was to determine which (if any) characteristics can predict successful response to acupuncture in chronic pain patients treated at military treatment facilities. Methods: Data from 222 patients who received treatment for a chronic pain condition were collected from 2 medical centers. The patients underwent at least 4 acupuncture treatments and had an average pain score of 4 or higher on a 0- to 10-point numerical rating scale or visual analog scale in the week before treatment initiation. A successful outcome was defined to be a 2-point or greater reduction on the numerical rating scale or visual analog scale 12 weeks postinitial treatment. Results: The overall treatment success rate was 42.3%. Multivariate logistic regression found a higher baseline pain rating and the use of stimulation needles to be associated with a positive outcome (odds ratio [OR]=1.26; 95% confidence interval [CI], 1.03-1.55; P =0.02 and OR=2.73; 95% CI, 1.39-5.32; P =0.03, respectively). Only the presence of one or more psychological comorbidities was found to be associated with treatment failure (OR=0.67; 95% CI, 0.49-0.92; P =0.01). Discussion: The use of electrical stimulation and higher baseline pain score were associated with a positive treatment outcome, while the presence of a psychological comorbidity diminished the likelihood of treatment success. Practitioners should consider using electrical stimulation more frequently, and addressing psychopathology before or concurrent to treatment, when initiating acupuncture.